Molecular alterations during larval development of Haemonchus contortus in vitro are under tight post-transcriptional control. Issue 9 (August 2018) - Ma, Guangxu; Wang, Tao; Korhonen, Pasi K.; Ang, Ching-Seng; Williamson, Nicholas A.; Young, Neil D.; Stroehlein, Andreas J.; Hall, Ross S.; Koehler, Anson V.; Hofmann, Andreas; Gasser, Robin B.
Graphical abstract: Highlights: Integrated transcriptomic, proteomic and bioinformatic analysis. Larval development of Haemonchus contortus in vitro. Molecular alterations are under tight post-transcriptional control. Abstract: In this study, we explored the molecular alterations in the developmental switch from the L3 to the exsheathed L3 (xL3) and to the L4 stage of Haemonchus contortus in vitro using an integrated transcriptomic, proteomic and bioinformatic approach. Totals of 9, 754 mRNAs, 88 microRNAs (miRNAs) and 1, 591 proteins were identified, and 6, 686 miRNA-mRNA pairs inferred in all larval stages studied. Approximately 16% of transcripts in the combined transcriptome (representing all three larval stages) were expressed as proteins, and there were positive correlations ( r  = 0.39–0.44) between mRNA transcription and protein expression in the three distinct developmental stages of the parasite. Of the predicted targets, 1, 019 (27.0%) mRNA transcripts were expressed as proteins, and there was a negative correlation ( r  = −0.60 to −0.50) in the differential mRNA transcription and protein expression between developmental stages upon pairwise comparison. The changes in transcription (mRNA and miRNA) and protein expression from the free-living to the parasitic life cycle phase of H. contortus related to enrichments in biological pathways associated with metabolism (e.g., carbohydrate and lipid degradation, and amino acid metabolism), environmental information processing (e.g., signal transduction, signalling molecules and interactions) and/or genetic information processing (e.g., transcription and translation). Specifically, fatty acid degradation, steroid hormone biosynthesis and the Rap1 signalling pathway were suppressed, whereas transcription, translation and protein processing in the endoplasmic reticulum were upregulated during the transition from the free-living L3 to the parasitic xL3 and L4 stages of the nematode in vitro. Dominant post-transcriptional regulation was inferred to elicit these changes, and particular miRNAs (e.g., hco-miR-34 and hco-miR-252 ) appear to play roles in stress responses and/or environmental adaptations during developmental transitions of H. contortus . Taken together, these integrated results provide a comprehensive insight into the developmental biology of this important parasite at the molecular level in vitro. The approach applied here to H. contortus can be readily applied to other parasitic nematodes.